Inclusive language and environment to welcome lesbian, gay, bisexual, transgender, queer, questioning, intersex, and asexual+ patients (Fertility and sterility, 2024)
Using inclusive language and creating an inclusive clinical environment to serve lesbian, gay, bisexual, transgender, queer, questioning, intersex, and asexual+ patients is vital to optimizing access to care and patient outcomes. Practical recommendations are made for increasing inclusivity in the clinic, and a glossary of current terms is included.